2014
DOI: 10.1111/j.1532-950x.2014.12304.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Mortality and Long‐Term Survival in 80 Dogs and 32 Cats Undergoing Excision of Thymic Epithelial Tumors

Abstract: While there is substantial risk of perioperative death in dogs and cats undergoing surgery for TETs, many animals that survive to discharge have prolonged survival. Survival is significantly decreased in dogs with paraneoplastic syndromes or incomplete histologic margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 34 publications
2
41
2
Order By: Relevance
“…Our earlier report on MG in cats documented a greater association of a cranial mediastinal mass in MG in cats compared with MG in dogs 3. The incidence of acquired MG in cats evaluated primarily for thymoma is between 4.7 and 6% of cases 21, 22. On the basis of the relatively common association of MG and thymoma as shown in our study, we recommend AChR antibody testing on all cats with confirmed or suspected thymoma.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Our earlier report on MG in cats documented a greater association of a cranial mediastinal mass in MG in cats compared with MG in dogs 3. The incidence of acquired MG in cats evaluated primarily for thymoma is between 4.7 and 6% of cases 21, 22. On the basis of the relatively common association of MG and thymoma as shown in our study, we recommend AChR antibody testing on all cats with confirmed or suspected thymoma.…”
Section: Discussionmentioning
confidence: 50%
“…Reports of outcomes are limited 34, 41. One study suggests a median survival time of 720 days in cats undergoing radiation therapy41 versus 3.71 years in cats undergoing surgery for thymoma 22. There is no information about the effect on clinical signs of MG in cats treated for thymoma with radiation treatment or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Cats with thymoma often present with respiratory signs; however, skin lesions are occasionally the presenting complaint . Multiple cases of thymoma‐associated cutaneous PNS have been reported, and the clinical presentations all were consistent with exfoliative dermatitis .…”
Section: Discussionmentioning
confidence: 99%
“…For example, dogs with myasthenia gravis and megaesophagus have a poor Video-Assisted Thoracic Surgery, Thoracoscopy short-term outcome. 11,14,16 Preoperative computed tomography (Fig. 5) is strongly advised in preoperative case selection for confirmation of noninvasiveness.…”
mentioning
confidence: 99%
“…Traditionally, resection of cranial mediastinal masses (CMMs) has been accomplished via median sternotomy or intercostal thoracotomy. [11][12][13][14] Recently, a VATS approach to CMM resection in two dogs was reported. 15 A VATS approach to CMM resection is feasible and associated with low operative morbidity, although ultimate prognosis depends on the underlying disease.…”
mentioning
confidence: 99%